Pengaruh Faktor-Faktor Keuangan dan Board Of Directors Characteristics Terhadap Nilai Perusahaan - Vergadilian Ivanhu Diedra; Lidya Agustina (Jurnal Akuntansi, 2021)
Abstract The purpose of this study was to examine the financial factors and board of directors characteristics on firm value. This research was conducted to obtain an overview of financial and non-financial factors influencing the value of the company during the Covid- 19 pandemic. The population of this study is Kompas 100 Index companies members for the 2019-2020 period, with a final sample of 72 companies. This study uses secondary data, and multiple linear regression analysis techniques. The results of this study show that Profitability and Board Meetings have a positive influence on firm value, while Company Size, Capital Structure, Board Independence, Board Size, and Gender Diversity have no effect on Firm Value and CEO Duality is only slightly present in Indonesia because Indonesia adheres to a two-tier system. Keywords: Firm Value, Financial Factors, and Non-financial Factors